Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. F. (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M.F. F (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G; Abreu, José M F (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus

Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus